2011
DOI: 10.1037/a0021150
|View full text |Cite
|
Sign up to set email alerts
|

Transitivity of preferences.

Abstract: Transitivity of preferences is a fundamental principle shared by most major contemporary rational, prescriptive, and descriptive models of decision making. To have transitive preferences, a person, group, or society that prefers choice option x to y and y to z must prefer x to z. Any claim of empirical violations of transitivity by individual decision makers requires evidence beyond a reasonable doubt. We discuss why unambiguous evidence is currently lacking and how to clarify the issue. In counterpoint to Tve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
330
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(350 citation statements)
references
References 109 publications
18
330
0
2
Order By: Relevance
“…Thus, when empirically obtained, such violations offer important theoretical constraints. Although WST violations have been reported in humans (11), recent research has shown that the vast majority of these putative violations were not statistically significant when a more appropriate statistical test is applied (20,22). It is thus an empirical question whether intransitivity, as predicted by our framework, will occur in human observers.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Thus, when empirically obtained, such violations offer important theoretical constraints. Although WST violations have been reported in humans (11), recent research has shown that the vast majority of these putative violations were not statistically significant when a more appropriate statistical test is applied (20,22). It is thus an empirical question whether intransitivity, as predicted by our framework, will occur in human observers.…”
Section: Resultsmentioning
confidence: 96%
“…For w > 0, the alternative with two (out of three) winning attributes (A) will (on average) be chosen over an alternative that wins by a larger margin on a single attribute (B), because the input to the latter is more often dampened yielding a lower cumulative value. Thus, when the same three values are permuted circularly in three alternatives, the model predicts a violation of "weak stochastic transitivity" (WST) (11,20): A is chosen more often over B, B over C, and C over A (Fig. 1B; Table S2 for an illustration).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…which the votrix is monotone implies the property of strong stochastic transitivity [138]. A weaker property, usually referred to as weak stochastic transitivity, has also called the attention of researchers [136].…”
Section: Remark 518mentioning
confidence: 99%